Serum HER-2 concentration is associated with insulin resistance and decreases after weight loss - Moreno-Navarrete José; Frühbeck Gema; Menendez Javier A; Fernández-Real José; Vazquez-Martín Alejandro; Ricart Wifredo (Nutrition & Metabolism, 2010)
Abstract Background HER2/neu is a member of the epidermal growth factor receptor family easily detectable in the serum of cancer patients. We aimed to evaluate circulating HER-2 concentrations in association with insulin resistance in healthy and obese subjects. Methods Insulin sensitivity (minimal model) and serum HER-2 concentrations were evaluated in a cross sectional study in men (cohort 1, n = 167) and longitudinally after weight loss in obese subjects (cohort 2, n = 30). Results Serum HER-2 concentrations were positively associated with BMI and waist circumference (both r = 0.18, p = 0.02), post-load glucose (r = 0.28, p = 0.001) and fasting triglycerides (r = 0.26, p = 0.001); and negatively associated with insulin sensitivity (r = -0.29, p = 0.002, n = 109). Subjects with type 2 diabetes showed significantly increased soluble serum HER-2 concentrations. In different multivariate regression models, fasting triglycerides emerged as the factor that independently contributed to 10-11% of serum HER-2 variance. Serum HER-2 concentrations correlated significantly with fasting triglycerides and insulin sensitivity index in subjects from cohort 2. Weight loss led to a significant decrease of serum HER-2 concentrations. The change in serum HER-2 concentrations were significantly associated with the change in percent body fat and fasting triglycerides in young (below the median age of the cohort) subjects. Conclusions Serum HER-2 concentrations might be implicated in the pathophysiology of insulin resistance and associated comorbidities.